2010
DOI: 10.1007/s00586-010-1589-1
|View full text |Cite
|
Sign up to set email alerts
|

Posterior approach for cervical fracture–dislocations with traumatic disc herniation

Abstract: In the treatment algorithm for cervical spine fracture-dislocations, the recommended approach for treatment if there is a disc fragment in the canal is the anterior approach. The posterior approach is not common because of the disadvantage of potential neurological deterioration during reduction in traumatic cervical herniation patients. However, reports about the frequency of this deterioration and the behavior of disc fragments after reduction are scarce. Forty patients with traumatic disc herniation were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 32 publications
(43 reference statements)
0
50
0
4
Order By: Relevance
“…An anterior cervical approach is recommended for a disc herniation in patients without a complete neurological deficit as it allows direct decompression, avoiding neurological deterioration with an eventual indirect decompression achieved with a posterior laminectomy 1,15,24 . In the past, this was an absolute indication for an anterior approach, but Nakashima et al reported a series of 40 patients with traumatic cervical herniation treated by a posterior approach without need of anterior cervical surgery, suggesting that the risk of neurological deterioration may be less than reported previously (Level of Evidence: III) 23 .…”
Section: Advantages and Indicationsmentioning
confidence: 94%
See 4 more Smart Citations
“…An anterior cervical approach is recommended for a disc herniation in patients without a complete neurological deficit as it allows direct decompression, avoiding neurological deterioration with an eventual indirect decompression achieved with a posterior laminectomy 1,15,24 . In the past, this was an absolute indication for an anterior approach, but Nakashima et al reported a series of 40 patients with traumatic cervical herniation treated by a posterior approach without need of anterior cervical surgery, suggesting that the risk of neurological deterioration may be less than reported previously (Level of Evidence: III) 23 .…”
Section: Advantages and Indicationsmentioning
confidence: 94%
“…23 Anterior approaches have the advantages of supine position, less surgical trauma, and direct anterior decompression of neural elements, such as a disk herniation or an anterior located bone fragment (Level of Evidence: III) 23 . Kwon et al reported that patients treated with anterior cervical discectomy and fusion (ACDF) for unilateral facet fracture-dislocation had slightly less pain in the postoperative period, a lower rate of wound infection, a higher rate of radiological bone union, with a better cervical alignment compared with those treated with a posterior approach (Level of Evidence: II) 9 .…”
Section: Advantages and Indicationsmentioning
confidence: 99%
See 3 more Smart Citations